2021
DOI: 10.21203/rs.3.rs-234844/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

E-learning-based medical education during COVID19 pandemic From Medical students' View Points

Abstract: Background Most universities around the world have replaced e-learning with face-to-face methods after Covid-19 Pandemic. The present study evaluates the students' viewpoints about the dimensions of e-learning during the COVID-19 pandemic. Methods This is a survey study aimed at investigating e-learning experiences of 550 students of Shiraz University of Medical Sciences(SUMS) during the time Coronavirus pandemic. To data collection, a research-made questionnaire was employed, and the data were analyzed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…Jensen et al state that only the use of face-to-face or electronic methods does not guarantee its effectiveness, but in fact, it is the amount of interaction between the teachers and the student that can make a combined course effective (56). In the research by Khojasteh et al, the results showed that the most important determining factor in the effectiveness of learning is the interactions between teacher and students (57).…”
Section: Discussionmentioning
confidence: 99%
“…Jensen et al state that only the use of face-to-face or electronic methods does not guarantee its effectiveness, but in fact, it is the amount of interaction between the teachers and the student that can make a combined course effective (56). In the research by Khojasteh et al, the results showed that the most important determining factor in the effectiveness of learning is the interactions between teacher and students (57).…”
Section: Discussionmentioning
confidence: 99%
“…On the positive side, this situation gives more spaces for lecturers to express their creativity in remote teaching and learning implementation. However, mental stress, lack of infrastructure, and less flexibility to interact among students and lecturers are some of challenges faced by educational institutions (Sia and Adamu, 2020;Khojasteh et al, 2021). In another study, Allam et al, 2020 found that the students' level of motivation and self-dependent learning are at low level.…”
Section: Introductionmentioning
confidence: 99%